A cross-national comparison in assessment of urban park soundscapes in France, Korea, and Sweden through laboratory experiments - Jeon, Jin Yong (2018)
This study aims at examining the effect of socio-cultural context, including language, on soundscape assessments in urban parks. In total, 95 persons took part in three laboratory experiments, conducted in France (30 participants), Korea (30 participants) and Sweden (35 participants). Twenty-eight audio-visual excerpts from recordings conducted in five urban parks were used as stimuli. The participants evaluated soundscape quality using attribute scales provided in their own native languages. Principal Components Analysis produced two principal components of perceived affective quality, Pleasantness and Eventfulness. There were high levels of similarity in attributes associated with the Pleasantness among the three countries, whereas some differences were observed in the attributes related to Eventfulness. Two hierarchical cluster analyses were conducted based on perceived dominance of sound sources, and component scores of perceived affective quality. There were no significant differences in clustering results based on perceived dominance of sound sources among the different nationalities. In contrast, discrepancies were found in the clustering results based on perceived affective quality. In particular, perceptual responses to human sounds, birdsong, and water sounds, which are closely related to Eventfulness, were significantly different across the three cultural backgrounds. These findings provide empirical evidence of socio-cultural differences in soundscape assessment.